2012
DOI: 10.1007/s10493-012-9513-5
|View full text |Cite
|
Sign up to set email alerts
|

How promising is Lasioseius floridensis as a control agent of Polyphagotarsonemus latus?

Abstract: The blattisociid mite Lasioseius floridensis Berlese was found associated with the broad mite, Polyphagotarsonemus latus (Banks), on gerbera leaves in Mogi das Cruzes, State of Sao Paulo, Brazil. Blattisociid mites are not common on aerial plant parts, except under high air humidity levels. Some Lasioseius species have been mentioned as effective control agents of rice pest mites, but nothing is known about the biology of L. floridensis. The objective of this study was to evaluate whether the observed co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
3
12
0
Order By: Relevance
“…They have higher fecundity when females were fed on free living nematode, R. sccanica than feeding on R. robini. The present agrees with obtained results by Britto et al, (2012), they found that the fecundity of Lasioseius floridensis Berlese was 3 times higher when fed on the free living nematode rather than Tyrophagus putrescentiae (Schrank). Somespecies of Ascidae and Macrochelidae are so reliant on nematodes as food.…”
Section: Discussionsupporting
confidence: 93%
“…They have higher fecundity when females were fed on free living nematode, R. sccanica than feeding on R. robini. The present agrees with obtained results by Britto et al, (2012), they found that the fecundity of Lasioseius floridensis Berlese was 3 times higher when fed on the free living nematode rather than Tyrophagus putrescentiae (Schrank). Somespecies of Ascidae and Macrochelidae are so reliant on nematodes as food.…”
Section: Discussionsupporting
confidence: 93%
“…Development and reproduction on R. robini were reported for L. africanus (Mowafi 2005 ), L. athiasae (Nasr et al 1990b ) and L. allii (= bispinosus ) (Nawar et al 1990 ;Lesna et al 1995 ). Similarly, development and reproduction on T. putrescentiae were reported for L. africanus (Mowafi 2005 ), L. athiasae (Nasr et al 1990a ), L. allii (= bispinosus ) (Nawar et al 1990 ), L. dentatus (Fouly 1997 ), L. fl oridensis (= fi metorum ) (Enkegaar and Broodsgaard 2000 ;Britto et al 2012 ), Lasioseius sewai Nasr and Abou-Awad ) and unidentifi ed Lasioseius species (Wu et al 2009 ;Xu 2011 (Britto et al 2012 ), Lasioseius lindquisti Nasr and Abou-Awad on A. dioscoridis (Momen et al 2011 ), an unidentifi ed Lasioseius on C. lactis , Rhizoglyphus echinopus (Fumouze and Robin) and Tetranychus kanzawai Kishida (Wu et al 2009 ) and Lasioseius zaheri Nasr on T. putrescentiae (Nawar and El-Sherif 1992 ). In a comparative study, Lo and Ho ( 1984 ) observed quicker development and higher oviposition and predation rates of L. youcefi on an unidentifi ed Tarsonemus than on S. spinki Smiley, both tarsonemids from rice.…”
Section: Meloidogyne Javanicamentioning
confidence: 81%
“…Pollen of Phoenix dactylifera L. was reported to allow development and reproduction of L. lindquisti (Momen et al 2011 ). However, pollen of Ricinus communis L. did not promote the oviposition of L. lindquisti (Momen et al 2011 ) or of L. fl oridensis (Britto et al 2012 ), although it allowed immature development of the former species. Thus, acceptance of pollen may vary according to the Lasioseius species and, probably according to the type of pollen offered.…”
Section: Meloidogyne Javanicamentioning
confidence: 84%
See 2 more Smart Citations